2013
DOI: 10.1093/fampra/cmt027
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a peer-support intervention for people with type 2 diabetes: a qualitative study

Abstract: This study revealed that it was feasible to implement a peer-support intervention in the general practice setting. Challenges of delivering such an intervention were identified, particularly in relation to meeting attendance, and should be considered in further research in the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 13 publications
1
31
0
2
Order By: Relevance
“…This is based on the belief that individuals are socially embedded, where social relations constitute an individual’s identity and this is reaffirmed or discredited through interaction with others. Since the PSWs’ emerging identity is dependent on this interaction, it was seen to engender a sense of purpose and increased self esteem [ 9 , 11 , 12 , 19 , 21 , 22 , 25 , 33 35 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is based on the belief that individuals are socially embedded, where social relations constitute an individual’s identity and this is reaffirmed or discredited through interaction with others. Since the PSWs’ emerging identity is dependent on this interaction, it was seen to engender a sense of purpose and increased self esteem [ 9 , 11 , 12 , 19 , 21 , 22 , 25 , 33 35 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The value of peer support models for improving client access, uptake and engagement with health services and for adding value to the client experience is widely recognised. Their success has been replicated in engagement with hard to reach groups from middle aged men with chronic disease [ 17 21 ], to those with stigmatised disease [ 16 , 22 25 ] and people who misuse substances [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Across the literature, there is a large variation in the training offered to volunteers in the amount of hours and in the content delivered. Similar research with volunteers has reported training durations ranging from 5 hours in some studies27 to 50 hours in others 28. The intensity of the training is dependent on the nature of the peer supporters’ role.…”
Section: Discussionmentioning
confidence: 62%
“…Other than requiring a dedicated staff member, currently little is known about the specifics and amount of supervision needed for peer supporter roles for optimal retention and effectiveness,35 with some literature reporting a member of the research team contacting peer supporters monthly by phone 13 27. Simmons et al 26 reported a 50% withdrawal rate of volunteers after a 2-month period, compared with an 11% withdrawal rate over a similar time period in this program.…”
Section: Discussionmentioning
confidence: 99%
“…Using peers to educate other patients with T2D has shown effective in providing ongoing support over a longer period. 31 32 In this study, volunteer patients with T2D are recruited through the Danish Diabetes Association, where a consultant contacts possible patients via email. The Interval Walking Ambassadors do IWT locally in phase II with patients from the IWTsupport group.…”
Section: Methods and Analysismentioning
confidence: 99%